PENGARUH MODEL COOPERATIVE LEARNING TIPE EXAMPLE NON-EXAMPLE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA - Siti Aisah; Salati Asmahasanah (Attadib: Journal of Elementary Education, 2018)
This study aims to find out the learning outcomes of students applying Cooperative Learning model type Example Non Example and using only conventional learning in science subjects class V in MI Tarbiyatusshibyan Bogor, and know how the influence of the implementation of Cooperative Learning model type Example Non Example against science subjects in class V MI Tarbiyatusshibyan Bogor. This research is quantitative descriptive with experimental design "Qusi Experiment". The population in this study is all students of class V MI Tarbiyatusshibyan Bogor with the number of 40 students, this study sample is a class A student with the number of students 20 and B with the number of students 20. Data collected through tests, namely pre-test and post-test in the class control and experiment with multiple choice questions. The results obtained from this research that the implementation of cooperative learning model type examples nin examples significantly influence the results of learning ipa. That the value of test result t that is in the experimental class obtained value -t arithmetic> -t table (-8.393> -2.090), then Ha accepted and Ho rejected. while in the control class obtained t arithmetic> -t table (-7.054> -2.090), then Ha accepted and Ho rejected. So it can be concluded that the application of learning models examples non examples have an influence on student learning outcomes.